2022
DOI: 10.1123/jpah.2022-0243
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity Among Adults in Botswana: Sociodemographic Factors, Health Status, and Body Image

Abstract: Background: Growing evidence of lower physical activity (PA), higher sedentary behavior, and prevalence of overweight and obesity in African countries calls for more research on PA behavior and its various correlates in this context. This study examined the proportion of adults meeting World Health Organization PA guidelines from 3 urban regions of Botswana, as well as the relationship among sociodemographic factors, body image, and participation in moderate to vigorous PA. Methods: Using a 2-stage stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In urban Ethiopia, 61 % of participants reported accumulating 30–60 min of physical activity ‘frequently or very frequently’ (23) and 76 % reported engaging in physical activity ‘sometimes or often’ in urban Ghana (107) . WHO physical activity recommendations were met by 46 % in urban Botswana (116) , 50 % in rural Nigeria (34) and 86 % in urban South Africa (110,112) (but only by 48 % of staff in a private hospital in South Africa (113) ). However, 62 % of urban residents in Ghana (35) , 72 % of participants in four Kenyan regions and 80 % of South African taxi drivers did not report any regular exercise (84,102) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban Ethiopia, 61 % of participants reported accumulating 30–60 min of physical activity ‘frequently or very frequently’ (23) and 76 % reported engaging in physical activity ‘sometimes or often’ in urban Ghana (107) . WHO physical activity recommendations were met by 46 % in urban Botswana (116) , 50 % in rural Nigeria (34) and 86 % in urban South Africa (110,112) (but only by 48 % of staff in a private hospital in South Africa (113) ). However, 62 % of urban residents in Ghana (35) , 72 % of participants in four Kenyan regions and 80 % of South African taxi drivers did not report any regular exercise (84,102) .…”
Section: Resultsmentioning
confidence: 99%
“…X: In contrast, a Malawian qualitative study among urban women found those with a normal weight were involved in weight control, while those who were overweight or obese were not controlling their weight (100) . p : Discontent and concerns about body appearance (weight and size) were associated with lower physical activity engagement in Botswana (116) . may be due to a need to strike a balance between not being thin or too fat, as being thin may be associated with poor health (135) or poverty (37,91) , while being too fat may be perceived negatively (37,39,79) .…”
Section: Knowledge On Risk Factormentioning
confidence: 97%
“…At the same time, young and middle-aged people are facing huge work and family pressures, changing lifestyles, and prevalent sedentary behaviors, which increase their risk for developing multiple health issues [ 4 ]. A large number of adults (54.2%) do not meet the WHO’s recommended level of physical activity [ 5 ], especially office workers, who maintain sedentary behaviors during the workday for 82.0% of the time [ 6 ].…”
Section: Introductionmentioning
confidence: 99%